RIG-I activating immunostimulatory RNA boosts the efficacy of anticancer vaccines and synergizes with immune checkpoint blockade - Heidegger, Simon; Kreppel, Diana; Bscheider, Michael; Stritzke, Florian; Nedelko, Tatiana; Wintges, Alexander; Bek, Sarah; Fischer, Julius C.; Graalmann, Theresa; Kalinke, Ulrich; Bassermann, Florian; Haas, Tobias; et al. (EBioMedicine, 2019)
Background: Antibody-mediated targeting of regulatory T cell receptors such as CTLA-4 enhances antitumor immune responses against several cancer entities including malignant melanoma. Yet, therapeutic success in patients remains variable underscoring the need for novel combinatorial approaches. Methods: Here we established a vaccination strategy that combines engagement of the nucleic acid-sensing pattern recognition receptor RIG-I, antigen and CTLA-4 blockade. We used in vitro transcribed 5′-triphosphorylated RNA (3pRNA) to therapeutically target the RIG-I pathway. We performed in vitro functional analysis in bone-marrow derived dendritic cells and investigated RIG-I-enhanced vaccines in different murine melanoma models. Findings: We found that protein vaccination together with RIG-I ligation via 3pRNA strongly synergizes with CTLA-4 blockade to induce expansion and activation of antigen-specific CD8 + T cells that translates into potent antitumor immunity. RIG-I-induced cross-priming of cytotoxic T cells as well as antitumor immunity were dependent on the host adapter protein MAVS and type I interferon (IFN-I) signaling and were mediated by dendritic cells. Interpretation: Overall, our data demonstrate the potency of a novel combinatorial vaccination strategy combining RIG-I-driven immunization with CTLA-4 blockade to prevent and treat experimental melanoma. Fund: German Research Foundation (SFB 1335, SFB 1371), EMBO, Else Kröner-Fresenius-Foundation, German Cancer Aid, European Hematology Association, DKMS Foundation for Giving Life, Dres. Carl Maximilian and Carl Manfred Bayer-Foundation.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Anti-cancer vaccine; Dendritic cells; Immune checkpoint inhibitors; Immuno-oncology; Innate immunity; RIG-I